2001
DOI: 10.1179/acb.2001.055
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity Related to Itraconazole : Report of Three Cases

Abstract: Itraconazole-induced liver injury presents with a cholestatic pattern of injury with damage to the interlobular bile ducts, possibly leading to ductopenia. We suggest that itraconazole should be added to the list of drugs that may be responsible for a drug-induced vanishing bile duct syndrome. Further histologic documentation in other cases is necessary to strengthen our current findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
2
17
0
1
Order By: Relevance
“…In addition, the liver biopsy specimens from patients with ITZ-induced liver injury showed histological patterns of cholestasis (Adriaenssens et al, 2001). In the present study, in patients 1, 2, and 3, ALP, ␥-GTP, and total bilirubin were increased during ITZ-administration (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, the liver biopsy specimens from patients with ITZ-induced liver injury showed histological patterns of cholestasis (Adriaenssens et al, 2001). In the present study, in patients 1, 2, and 3, ALP, ␥-GTP, and total bilirubin were increased during ITZ-administration (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…An analysis of the Food and Drug Administration Adverse Event Reporting System database (http://www.fda.gov/ Drugs/GuidanceComplianceRegulatoryInformation/Surveillance/ AdverseDrugEffects/) revealed that antimycotics are involved in approximately 3% of all DILI cases (Raschi et al, 2014). Moreover, antifungal azoles have been associated with elevated levels of serum liver enzymes as well as liver injury occasionally leading to liver failure (Hann et al, 1993;Gearhart, 1994;Adriaenssens et al, 2001;Chang et al, 2007). Therefore, we MDR3 Inhibition by Antifungals first tested the interaction of five clinically used antifungal azoles with MDR3: fluconazole, itraconazole, ketoconazole, posaconazole, and voriconazole.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of itraconazole prophylaxis has been demonstrated in other immunocompromised patient populations, and it has been demonstrated to be similar to fluconazole in reducing fungal colonization in liver-transplant patients (20 -23). With the current clinical experience indicating that itraconazole is well tolerated with rarely reported cases of hepatotoxicity, we proceeded to study its efficacy in the liver-transplant population (24).…”
Section: Safety Evaluationmentioning
confidence: 99%